2021
DOI: 10.1002/pros.24287
|View full text |Cite
|
Sign up to set email alerts
|

How socioeconomic and clinical factors impact prostate‐cancer‐specific and other‐cause mortality in prostate cancer stratified by clinical stage: Competing‐risk analysis

Abstract: Background The aim of this study was to analyze the causes of death and risk factors of prostate‐cancer‐specific mortality (PCSM) and other‐cause mortality (OCM) at different clinical stages using data from the Surveillance, Epidemiology, and End Results database. Methods The characteristics and cause‐specific death classifications of males with prostate cancer (PCa) were extracted. Multivariate competing‐risk regression analysis was used to identify significant predictors and quantify the cumulative incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Additionally, T2 stage patients had better prognosis compared to T1 patients, and this may be due to the heterogeneity of PCa, with some T1 patients showing a worse outcome than those with T2 stage ( 28 ). In the present study, patients with higher SES scores were associated with a better outcome, which was consistent with the result of previous studies ( 20 , 29 ). A higher SES score suggests a better socio-economic status.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Additionally, T2 stage patients had better prognosis compared to T1 patients, and this may be due to the heterogeneity of PCa, with some T1 patients showing a worse outcome than those with T2 stage ( 28 ). In the present study, patients with higher SES scores were associated with a better outcome, which was consistent with the result of previous studies ( 20 , 29 ). A higher SES score suggests a better socio-economic status.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that age at diagnosis was an influencing factor for mortality in patients with localized PCa. A similar result was reported in a previous competing risk regression analyze on mortality data ( 19 , 20 ). An increased risk of it with an elevated age at the time of diagnosis for older adults.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations